Pengaruh Pemberian Fraksi Protein Ekstrak Kuda Laut (Hippocampus kuda Bleeker, 1852) terhadap Peningkatan Kadar Hemoglobin Mencit (Mus musculus L) - Adam, Kindi; Fitria, Laksmindra; Sarto, Mulyati (Jurnal Kefarmasian Indonesia, 2014)
Seahorse (Hippocampus kuda) is known to have a high concentration of iron, taurin and progesteron as testosteron precursor. Seahorse extract can increase the production of testosterone hormone of mice. On the erythrocytes development, kidney is stimulated to release erythropoietin hormone in case of hypoxia and also related with testosterone production. Erythropoietin control erythrocytes development and increase hemoglobin synthesis. The objective of experiment was to study the effect of seahorse extract as supplemented food in optimal concentration in range of 100, 200 and 300 mg/kg body weight on mice’s hematopoiesis and erythropoiesis. Each of treatment groups consist of 5 mices. The observed parameters were hematocrit value, hemoglobin concentration and renal index which observed on day 0, 34 and 67. The result showed that treatment of seahorse protein fraction extract until 300 mg/kg body weight dosage have no effect to the hematocrit value. The 200 mg/kg body weight extract dosage was able to increase the hemoglobin rate measurement. Renal index of Mice on day 34 and 67 after treatment did not give significant difference among treatment and control